Analisis Kualitas Air Embung Bendo, Mayangkawis dan Babo dengan Peruntukan Wisata dan Pertanian di Kabupaten Bojonegoro: Analysis of Water Quality of Bendo, Mayangkawis and Babo Reservoirs for Tourism and Agriculture in Bojonegoro Regency - Nurfarikha, Elza Dianis; Sitogasa, Praditya Sigit Ardisty (Media Ilmiah Teknik Lingkungan (MITL), 2024)
With the potential of the agricultural sector, Bojonegoro Regency certainly requires an abundant supply of clean water. To overcome this problem, the Bojonegoro Regency Government built reservoirs to protect clean water supply in several areas in Bojonegoro Regency. The utilization of existing embung in Bojonegoro is not limited to agriculture only, but also as a tourist spot. To date, there has been no research assessing the quality of water in reservoirs. Consequently, this study aimed to evaluate the water quality in three reservoirs located in Bojonegoro. This study employs qualitative analysis derived from the environmental laboratory water quality assessments conducted by Dinas Lingkungan Hidup Kabupaten Bojonegoro. The findings from the water analyses of Embung Bendo, Embung Mayangkawis, and Embung Babo reveal distinct conditions among the three locations. These variations are attributed to differing environmental factors that influence each site uniquely.